Two new species of the genus Rakovicius Pittino, 2006 (Coleoptera: Scarabaeidae: Aphodiinae) - Minkina, Łukasz; Skelley, Paul (Zootaxa, 2025)
Two new species of the genus Rakovicius Pittino, 2006: R. neimongolensis Minkina & Skelley, sp. nov. from China (Nei Mongol), and R. sagaingensis Minkina & Skelley, sp. nov. from Myanmar are described and illustrated.